2021
DOI: 10.3390/polym13234097
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Soluble Chitosan Derivatives Nanoparticles for Vaccine: Synthesis, Characterization and Evaluation

Abstract: Herein, a novel chitosan derivative nanoparticle was proposed to function as a delivery carrier. First of all, an improvement was made to the way N-2-hydroxypropyl trimcthyl ammonium chloride chitosan (N-2-HACC) was synthesized. Moreover, the solution to one-step synthesis of N-2-HACC from chitosan (CS) was developed. Different from the previous report, the synthesis process was simplified, and there was a reduction in the amount of 2,3-epoxypropyl trimethyl ammonium chloride (EPTAC) used. With its excellent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Experimental studies have shown that the presence of nanoparticles can alter the molecular structure of composite materials by cross-linking with CS on the polymer chain. 48 Additionally, it has been observed that water molecule diffusion within the polymer network also has a significant impact.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Experimental studies have shown that the presence of nanoparticles can alter the molecular structure of composite materials by cross-linking with CS on the polymer chain. 48 Additionally, it has been observed that water molecule diffusion within the polymer network also has a significant impact.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Only in specific acidic liquids does the alkaline polysaccharide chitosan exhibit reasonably good solubility. Quaternization was used to alter chitosan to create quaternized chitosan, which increased its water solubility and expanded its uses [4][5][6][7]. Quaternary ammonium salt synthesis is a two-phase, solidliquid reaction that produces chitosan.…”
Section: Introductionmentioning
confidence: 99%